Efektivitas terapi guided imagery terhadap tingkat stres pada mahasiswa tingkat akhir dalam menyelesaikan karya tulis ilmiah - Syah, Afni Yan; Delianti, Nosi (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Students are individuals who are studying at a tertiary institution who have the task of completing their studies, within a predetermined time period, and will end their study period by compiling a scientific work as a graduation requirement. The process of preparing scientific work is not a simple thing for students. Students are required to be independent, critical, write scientifically, conduct field surveys, and apply the knowledge learned during the lecture process. Students feel that preparing scientific work is beyond their abilities so they easily experience stress. Stress management can be done with guided imagery therapy, which is a relaxation method for imagining places and events related to pleasant feelings of relaxation.Purpose: To determine the effectiveness of guided imagery therapy on stress levels in final year students in completing scientific work.Method: Using quasi-experimental research with a pretest and posttest control group design approach. The sampling technique used non-probability sampling, purposive sampling, totaling 68 respondents and divided into 2 groups, namely 34 participants in the experimental group and 34 participants in the control group. The instrument used to measure stress levels in final year students is the Perceived Stress Scale (PSS-10). The statistical test used is the Paired Sample T-test.Results: Obtained p-value = 0.000 (p<0.05) in the experimental group, which means that there is an influence of guided imagery therapy on the stress level of final year students in completing scientific papers. This can be seen from the decrease in the average stress level in the experimental group to 4.88 and in the control group to 0.23.Conclusion: Guided imagination therapy is effective on final year students' stress levels in completing scientific work.Suggestion: In this case, there needs to be support from the family and campus in order to deal with stress in final year students appropriately. Keywords: Emphasize; Guided Imagery; Student. Pendahuluan: Mahasiswa merupakan individu yang sedang belajar di perguruan tinggi yang memiliki tugas dalam menyelesaikan studinya, dalam jangka waktu yang telah ditetapkan, dan akan mengakhiri masa kuliahnya dengan menyusun karya tulis ilmiah (KTI) sebagai syarat kelulusan. Proses penyusunan KTI ini bukan hal yang sederhana bagi mahasiswa. Mahasiswa diharuskan untuk mandiri, kritis, menulis secara ilmiah, melakukan survei lapangan, dan menerapkan ilmu yang dipelajari selama proses perkuliahan. Mahasiswa merasa bahwa dari penyusunan KTI diluar kemampuannya, sehingga mereka mudah mengalami stres. Penanganan stres dapat dilakukan dengan terapi guided imagery yang merupakan metode relaksasi untuk mengkhayalkan tempat dan kejadian berhubungan dengan rasa relaksasi yang menyenangkan.Tujuan: Untuk mengetahui efektivitas terapi guided imagery terhadap tingkat stres pada mahasiswa tingkat akhir dalam menyelesaikan karya tulis ilmiah.Metode: Menggunakan penelitian quasy eksperimen dengan pendekatan pretest dan postest control group design. Teknik pengambilan sampel dengan nonprobability sampling jenis purposive sampling sebanyak 68 responden dan dibagi menjadi 2 kelompok yaitu 34 partisipan kelompok eksperimen dan 34 kelompok kontrol. Instrumen yang digunakan untuk mengukur tingkat stres pada mahasiswa tingkat akhir berupa Perceived Stress Scale (PSS-10). Uji statistik yang digunakan yaitu uji Paired Sample T-test.Hasil: Mendapatkan p-value = 0.000 (p<0.05) pada kelompok eksperimen yang berarti ada pengaruh terapi guided imagery terhadap tingkat stres pada mahasiswa tingkat akhir dalam menyelesaikan karya tulis ilmiah. Hal ini dapat dilihat dari penurunan tingkat stres rerata pada kelompok eksperimen 4.88 dan pada kelompok kontrol 0.23.Simpulan: Terapi guided imagery efektif terhadap tingkat stres pada mahasiswa tingkat akhir dalam menyelesaikan KTI.Saran: Dalam hal ini perlu adanya dukungan dari keluarga dan pihak kampus agar dapat mengatasi stres pada mahasiswa tingkat akhir secara tepat. Kata Kunci: Guided Imagery; Mahasiswa; Stres.